2008
DOI: 10.1111/j.1524-475x.2008.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell stabilizer ketotifen prevents development of excessive skin wound contraction and fibrosis in red Duroc pigs

Abstract: Skin wound healing in Yorkshire pigs closely approximates human wound healing. Conversely, red Duroc pigs form fibroproliferative, hypercontractile scars. As mast cells have been implicated in several fibrotic conditions, the present study used these models to evaluate the potential role of mast cells in wound contraction and fibrosis. Immediately following the creation of full-thickness excisional wounds, the mast cell stabilizer ketotifen was used to treat both Yorkshire and red Durocs. Control red Durocs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 34 publications
1
91
0
Order By: Relevance
“…54 Reduced wound contraction and scar formation were reported in ketotifen-treated animals. Scars from pigs receiving ketotifen also displayed thinner and less dense collagen fibers and reduced numbers of alpha-smooth muscle actin-positive myofibroblasts.…”
Section: The Role Of Mast Cells In Scarring and Fibrosis In Mature Timentioning
confidence: 98%
See 1 more Smart Citation
“…54 Reduced wound contraction and scar formation were reported in ketotifen-treated animals. Scars from pigs receiving ketotifen also displayed thinner and less dense collagen fibers and reduced numbers of alpha-smooth muscle actin-positive myofibroblasts.…”
Section: The Role Of Mast Cells In Scarring and Fibrosis In Mature Timentioning
confidence: 98%
“…These include drugs like cromolyn (disodium cromoglycate) and ketotifen, which have shown promise in animal models. 54,59,60 However, while these drugs are able to prevent mast cell degranulation, they may also affect other cell types and it is unclear whether the release of mast cell mediators via secretory vesicles is affected by Figure 6. Methods to target mast cells.…”
Section: Targeting Mast Cells To Reduce Scarringmentioning
confidence: 99%
“…Given such pharmacological properties of ketotifen, the administration of this drug could also be useful in the treatment of organ fibrosis in addition to its primary efficacy for allergic diseases. Recently, several animal studies have actually shown the therapeutic efficacy of ketotifen in the treatment of post-traumatic dermal or joint capsular fibrosis [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Ketotifen has been FDA approved as an adjuvant treatment for adult and pediatric populations with asthma for over 15 years and more recently has been FDA approved for treatment of allergic conditions of the eye [16]. Ketotifen administration has also been shown to impair abnormal wound fibrosis and hypercontractile scar formation in the red Duroc pig [17]. Recently, we have shown in a rabbit model that treatment with ketotifen significantly reduced the biomechanical severity of post-traumatic joint contractures [18], although the effects of ketotifen treatment at the molecular level in this animal model have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%